Таксономическая ревизия клещей семейства Rhodacaridae Oudemans, 1902 (Parasitiformes, Gamasina) - Щербак, Г.И. (Вестник зоологии, 1979)
The paper gives the critical analysis of taxonomy of Rhodacaridae representatives
and their diagnostic characters. Diagnosis, description and identification key of genera
and subfamilies of Rhodacaridae O u d ms., 1902 stat. nov. are presented.